2016
DOI: 10.1007/s00775-016-1342-2
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) binding properties of hepcidin

Abstract: Hepcidin is a peptide hormone that regulates the homeostasis of iron metabolism. The N-terminal domain of hepcidin is conserved amongst a range of species and is capable of binding CuII and NiII through the amino terminal copper–nickel binding motif (ATCUN). It has been suggested that the binding of copper to hepcidin may have biological relevance. In this study we have investigated the binding of CuII with model peptides containing the ATCUN motif, fluorescently labelled hepcidin and hepcidin using MALDI-TOF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…It was suggested that copper was required for hepcidin activity, suggesting that perturbations in copper status could potentially alter iron metabolism via changes in hepcidin function. Another recent study, however, concluded that the level of interaction between HEPC and copper was likely insufficient to influence the ability of HEPC to regulate iron homeostasis (161). Moreover, the copper-binding properties of hepcidin-25 were recently utilized in the development of a novel detection assay for human hepcidin in serum (156).…”
Section: Intersection Of Iron and Copper Metabolism In The Livermentioning
confidence: 99%
“…It was suggested that copper was required for hepcidin activity, suggesting that perturbations in copper status could potentially alter iron metabolism via changes in hepcidin function. Another recent study, however, concluded that the level of interaction between HEPC and copper was likely insufficient to influence the ability of HEPC to regulate iron homeostasis (161). Moreover, the copper-binding properties of hepcidin-25 were recently utilized in the development of a novel detection assay for human hepcidin in serum (156).…”
Section: Intersection Of Iron and Copper Metabolism In The Livermentioning
confidence: 99%
“…As consequence, TfR1-mediated iron uptake is also reduced. Some studies have reported that hepcidin activity can be dependent on copper availability [77]; in fact, it has an “ATCUN” (amino-terminal Cu-Ni)-binding motif in the N-terminal of the mature protein capable to bind copper and nickel, even if a recent study has questioning this possibility [7779]. Tselepis et al highlighted that the incapacity of hepcidin to bind copper, drastically reduce the capacity of hepcidin to induce ferroportin degradation [77].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the decrease in hepcidin signal at molar ratio 1:5 and 1:10 coincides with significantly increased amounts of a new species identified further by MS/MS as the complex of hepcidin with two copper ions. This species was briefly mentioned previously in the literature [30], but no clear significance was attributed to the complex. To our best knowledge, this is the first reported chromatographic separation and MS/MS analysis of the peptide complex with two copper ions.…”
Section: Molecular Modellingmentioning
confidence: 98%
“…Analyzing the solution of hepcidin-Cu 2+ (molar ratio 1:10) revealed a hepcidin-25 species complexed with two Cu 2+ -ions. This compound was previously reported in literature using MALDI-TOF analysis [30], but never separated and characterized using LC-MS/MS. The doubly, triply and quadruply charged quasi-molecular ions were observed at m/z 1456.1, 971.0 and 728.5, respectively, but the signal intensity was lower compared to the other two species (see Supplementary Material Fig.…”
Section: Ms/ms Characterization Of Hepcidin-25 and Hepcidin-25-coppermentioning
confidence: 99%
See 1 more Smart Citation